Isolation and identification of a halophilic and alkaliphilic microalgal strain - Liu,Chenxi; Liu,Jiali; Hu,Songmiao; Wang,Xin; Wang,Xuhui; Guan,Qingjie (PeerJ, 2019)
Halophilic and alkaliphilic microalgal strain SAE1 was isolated from the saline–alkaline soil of Songnen Plain of Northeast China. Morphological observation revealed that SAE1 has a simple cellular structure, single cell, spherical, diameter of four to six μm, cell wall of about 0.22 μm thick, two chloroplasts and one nucleus. Analysis of the phylogenetic tree constructed by 18S sequence homology suggests that SAE1 is highly homologous to Nannochloris sp. BLD-15, with only four base substitutions in the homologous region. SAE1 was initially considered as Nannochloris sp. Analysis of the halophilic and alkaliphilic characteristics of SAE1 indicates that it can grow under one M NaHCO3 and NaCl concentrations, with optimal growth under 400 mM NaHCO3 and 200 mM NaCl. The intracellular ultrastructure of SAE1 significantly changed after NaCl and NaHCO3 treatments. A large number of starch grains accumulated after treatment with 400 mM NaHCO3 in cells, but few were found after treatment with 200 mM NaCl and none in the living condition without treatment. We conjectured that one of the metabolic characteristics of alkaliphilic (NaHCO3) microalga SAE1 is the formation of massive starch grains, which induce glycerol anabolism and increase osmotic pressure, thereby enhancing its ability to resist saline–sodic conditions. This feature of alkaliphilic (NaHCO3) microalga SAE1 contributes to its growth in the carbonate soil of Songnen Plain.
Keywords: Sodium bicarbonate (NaHCO3); NaCl; 18S; Algae